2002
DOI: 10.2486/indhealth.40.135
|View full text |Cite
|
Sign up to set email alerts
|

An Ergonomic Questionnaire Survey on the Use of Computers in Schools.

Abstract: A questionnaire was sent out to elementary, junior high and high schools in Yokohama and Kawasaki Cities from January to March 1998 regarding the use of personal computers by pupils and students. The survey included the questions that asked how often and in what environment computers are used, whether any instructions are given as to their use, children's working posture, and the effect on health. The results show that most schools are slow to develop instructive programs from the environmental or ergonomic po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2006
2006
2009
2009

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 10 publications
(9 reference statements)
2
18
0
Order By: Relevance
“…School computers may be shared by two or more children, particularly in the younger age groups (Sotoyama et al 2002, Breen et al 2007. This implies that the screen may be angled to one or both viewers, which has been shown to affect muscle activity and be related to greater musculoskeletal discomfort in university students (Szeto and Sham 2008).…”
Section: School Computer Usementioning
confidence: 99%
See 2 more Smart Citations
“…School computers may be shared by two or more children, particularly in the younger age groups (Sotoyama et al 2002, Breen et al 2007. This implies that the screen may be angled to one or both viewers, which has been shown to affect muscle activity and be related to greater musculoskeletal discomfort in university students (Szeto and Sham 2008).…”
Section: School Computer Usementioning
confidence: 99%
“…In addition, there is ample evidence to show that many children are using school computers at workstations that are unsuitable for their morphology (Oates et al 1998, Zandvliet and Straker 2001, Sotoyama et al 2002, Dockrell et al 2007). The physical effects of this discrepancy may currently be mitigated by the relatively short duration of use at school (Oates et al 1998, Sotoyama et al 2002. However, neck, upper back and lower back pain have all been associated with school furniture features (Murphy et al 2007).…”
Section: Child Computer Use Environments Are Differentmentioning
confidence: 99%
See 1 more Smart Citation
“…They reported that less than 10% of schools were 'actively' incorporating ergonomics information into the computer education of the pupils. Similar to Lai (2000) and Sotoyama et al (2002), the authors of this paper were concerned that children were using computers to an increasing extent, but may not have received any ergonomics information about their use.…”
Section: Teachers' Awareness Of Computer-related Ergonomicsmentioning
confidence: 96%
“…The lack of continuing professional development related to health issues associated with computer use for school staff was also commented on. Sotoyama et al (2002) conducted a questionnaire survey of the use of computers in schools in Yokohama and Kawasaki cities. They reported that less than 10% of schools were 'actively' incorporating ergonomics information into the computer education of the pupils.…”
Section: Teachers' Awareness Of Computer-related Ergonomicsmentioning
confidence: 99%